Effects on Coagulation of Levonorgestrel- and Desogestrel-containing Low Dose Oral Contraceptives: a Cross-over Study - Middeldorp, Saskia; Meijers, Joost C. M.; van den Ende, Abraham E.; van Enk, Adam; Bouma, Bonno N.; Tans, Guido; Rosing, Jan; Prins, Martin H.; Büller, Harry R. (Thrombosis and Haemostasis, 2000)
Combined oral contraceptives (OC) are known to increase the risk of venous thromboembolism. The aim of this randomized, cycle-controlled, cross-over study in 28 healthy volunteers was to assess potential differences between the effects of an OC containing 150 µg levonorgestrel (as representative of the so-called second generation OC) and an OC containing 150 µg desogestrel (as representative of the third generation OC) in combination with 30 µg ethinylestradiol on several coagulation factors and markers of thrombin formation. All participants used each OC for two cycles, and were switched to the other OC after a washout period of two menstrual cycles. The plasma concentrations of factors II, VII, X, and fibrinogen significantly increased during use of both the levonorgestrel- and desogestrel-containing OC’s. The plasma concentrations of factor VIII increased, and of factor V decreased, changes which only reached statistical significance during the use of the desogestrel-containing OC. During exposure to the desogestrel-containing OC, as compared with the levonorgestrel-containing OC, both factor VII and factor II showed a greater increase (FVII: 32% and 12% respectively; p <0.0001; FII: 16% and 12% respectively; p = 0.048), whereas factor V showed a greater decrease (–11% and –3% respectively; p = 0.010). Only one of the markers for ongoing coagulation (prothrombin fragment 1+2) showed a significant increase during OC use, whereas concentrations of thrombin-antithrombin complexes and soluble fibrin remained unchanged. For these markers, there was no difference between the tested OC’s. We conclude that there are differences between the effects of levonorgestrel and desogestrel-containing OC’s on some coagulation factors. Whether these changes provide a biological explanation for the reported differences in venous thromboembolic risk is as yet unclear. The real challenge now becomes to define a pattern of changes in the various systems which, if affected simultaneously, may tip the hemostatic balance towards a prethrombotic state and may lead to overt clinical venous thromboembolism.
Keywords: Oral contraceptives; coagulation; factor VII; factor II; factor V